The Values of Tolerance Education in Surah Al-Baqarah Verse 256 and Its Implications for Interfaith Harmony - Abdur Rahman; Islamiyah Islamiyah (Global Education Journal, 2026)
The Qur'an was given to Muslims to be read and comprehended. Reading and understanding the Qur'an yields diverse understandings according to each individual's abilities. Muslims' understanding of the Qur'an will also give rise to diverse behaviors as interpretations of the Qur'an in the practice of life, both on the theological, philosophical, psychological, and cultural levels. This study aims to examine the role of the Bangkalan Regency Interfaith Harmony Forum (FKUB) in fostering values ​​of tolerance in society. The research method used is thematic interpretation with field research. The results of the study indicate that, first, the verses on interfaith harmony indicate that what God has determined regarding the essence of glory is the most appropriate, not what is fought over by many people because God is All-Knowing and All-Aware. Thus, humans should pay attention to what is ordered by the Creator of mankind, who is All-Knowing and knows them, as well as their welfare. Second, in Bangkalan Regency, verses on tolerance, or in the author's terminology, verses on interfaith harmony, have been well implemented. This is evident in the harmony of the Bangkalan community towards groups of different faiths.